2015
DOI: 10.1186/s13568-015-0106-7
|View full text |Cite
|
Sign up to set email alerts
|

Induction, expression and characterisation of laccase genes from the marine-derived fungal strains Nigrospora sp. CBMAI 1328 and Arthopyrenia sp. CBMAI 1330

Abstract: The capability of the fungi Nigrospora sp. CBMAI 1328 and Arthopyrenia sp. CBMAI 1330 isolated from marine sponge to synthesise laccases (Lcc) in the presence of the inducer copper (1–10 μM) was assessed. In a liquid culture medium supplemented with 5 μM of copper sulphate after 5 days of incubation, Nigrospora sp. presented the highest Lcc activity (25.2 U·L−1). The effect of copper on Lcc gene expression was evaluated by reverse transcriptase polymerase chain reaction. Nigrospora sp. showed the highest gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 41 publications
1
20
1
Order By: Relevance
“…D'souza-Ticlo et al [27] opined that cu 2+ can have a negative coefficient with other media components on biomass accumulation. Our result is in contrast with the work of Passarini et al [22] who reported high biomass production in the presence of copper sulphate for Nigrospora sp. CBMAI 1328.…”
Section: Effect Of Copper and Manganese Ions On Laccase Productioncontrasting
confidence: 99%
See 4 more Smart Citations
“…D'souza-Ticlo et al [27] opined that cu 2+ can have a negative coefficient with other media components on biomass accumulation. Our result is in contrast with the work of Passarini et al [22] who reported high biomass production in the presence of copper sulphate for Nigrospora sp. CBMAI 1328.…”
Section: Effect Of Copper and Manganese Ions On Laccase Productioncontrasting
confidence: 99%
“…In this present study, the media containing Cu 2+ concentrations beyond 0.05% (w/v) showed a significant decrease in laccase production and fungal growth. This may be attributed to the inhibitory effect of Cu 2+ at higher concentrations as equally observed by Passarini et al [22]. Our result is in agreement with the reports of Galhaup et al [34] and Stajic et al [37] who separately reported that the addition of CuSO 4 in various concentrations (1-10 mM) stimulated laccase production in T. pubescens, P. ostreatus HA1493, P. ostreatus HA1494 and P. eryngii.…”
Section: Effect Of Copper and Manganese Ions On Laccase Productionsupporting
confidence: 93%
See 3 more Smart Citations